The Mode of Knowledge in Science and Social Science: of Knowledge in Science and Social Science: A Philosophical Examination - Agbo, Joseph N. (EBSU Journal of Social Sciences and Humanities, 2021)
This paper is a critical reflection on the bogus claim made by modern science to be in possession of a procedural compass which any discipline or enquirer that wants to arrive at knowledge would need to grab. It also examines the hopeful, but failed attempt by the inaugurators of social science to follow this compass in their study of social phenomena. The paper laments that the idea of a “Scient ific Method” which would unify all the sciences was the major problem which social science had to confront. It discusses the possibility of a prescriptive methodology that would suffice all the sciences. It argues that the failure of the project of positivism need not lead to the anarchical and radically relativistic alternatives found in the works of some critics of Kantian foundationalism– men like Rorty, Kuhn, Feyerabend, Quine, etc. The paper, therefore, concludes by raising some fundament al questions against the postmodern rejection of foundationalism and the wonders which is better and plausible: the totalitarianism and hegemony of foundationalism or the relativism and anarchy of postmodernism?